2020
DOI: 10.1002/adfm.202004498
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐Induced Interfacial Structural Conversion of Graphene Oxide to Graphene at Macroscale

Abstract: The controllable adjustment of an ideal graphene structure on the surface/ interface is important to achieve many of the potential characteristics and applications of graphene. Here, a phenomenon is observed in which friction can induce the structural conversion of graphene oxide (GO) to graphene perfectly on a macroscale sliding interface. The controlling factors and molecular interaction mechanism are further revealed by experiments and theoretical simulation. The results show that shear force drives the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…MD simulation has also made many important contributions to the identification of chemical changes in friction and wear processes between solid interfaces. Gao et al [981] found that friction can induce the structural conversion of GO to graphene perfectly on a macroscale sliding interface. They used ReaxFF MD simulations to study the friction and wear process of GO (Fig.…”
Section: Tribochemistrymentioning
confidence: 99%
“…MD simulation has also made many important contributions to the identification of chemical changes in friction and wear processes between solid interfaces. Gao et al [981] found that friction can induce the structural conversion of GO to graphene perfectly on a macroscale sliding interface. They used ReaxFF MD simulations to study the friction and wear process of GO (Fig.…”
Section: Tribochemistrymentioning
confidence: 99%
“…In our simulations, we also observed a lot of functional groups detached from GO flakes during the sliding process, in agreement with the observation of GO reduction in tribological experiments. 14,42 To characterize the transfer behaviors of functional groups, we calculated the number of O atoms, originally from the functional groups, still bonded with C atoms of the GO flakes or transferred to Fe atoms of the substrates. This calculated value was further divided by the total number of functional groups to obtain the ratio of retained and transferred functional groups.…”
Section: Wear Process Of Go/grmentioning
confidence: 99%
“…39 Physical treatment can be employed to adjust electrode structures without changing the chemical properties, which is an ideal method to tune the interlayer structure. 40 Shear force, which is proven to adjust nanosheet orientation during polymer composite fabrication, is also considered in the graphene-based membrane preparation strategies. However, shear force has difficulty to solely control the orientation of nanosheets with regular distribution and enhanced interaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the inserted additive distribution and interlayer channel regularization strategies are urgently required to control the lamellar structure . Physical treatment can be employed to adjust electrode structures without changing the chemical properties, which is an ideal method to tune the interlayer structure . Shear force, which is proven to adjust nanosheet orientation during polymer composite fabrication, is also considered in the graphene-based membrane preparation strategies.…”
Section: Introductionmentioning
confidence: 99%